FLT-PET-CT for the Detection of Disease Recurrence After Stereotactic Ablative Radiotherapy or Hyperfractionation for Thoracic Malignancy: A Prospective Pilot Study - Hiniker, Susan M.; Sodji, Quaovi; Quon, Andrew; Gutkin, Paulina M.; Arksey, Natasha; Graves, Edward E.; Chin, Frederick T.; Maxim, Peter G.; Diehn, Maximilian; Loo, Billy W. (Frontiers in Oncology, 2019)
Differentiating local recurrence from post-treatment changes on PET scans following stereotactic ablative radiotherapy (SABR) or hyperfractionation for lung tumors is challenging. We performed a prospective pilot study of 3-deoxy-3-[18F]-fluorothymidine (FLT)-PET-CT in patients with equivocal post-radiation FDG-PET-CT to assess disease recurrence. Methods: We prospectively enrolled 10 patients, 9 treated with SABR and 1 with hyperfractionated external beam radiotherapy for thoracic malignancy with subsequent equivocal follow-up FDG-PET-CT, to undergo FLT-PET-CT prior to biopsy or serial imaging. FLT-PET scans were interpreted by a radiologist with experience in reading FLT-PET-CT and blinded to the results of any subsequent biopsy or imaging. Results: Of the 10 patients enrolled, 8 were evaluable after FLT-PET-CT. Based on the FLT-PET-CT, a blinded radiologist accurately predicted disease recurrence versus inflammatory changes in 7 patients (87.5%). The combination of higher lesion SUVmax and higher ratio of lesion SUVmax to SUVmax of mediastinal blood pool was indicative of recurrence. Qualitative assessment of increased degree of focality of the lesion also appears to be indicative of disease recurrence. Conclusion: Adjunctive FLT-PET-CT imaging can complement FDG-PET-CT scan in distinguishing post-treatment radiation changes from disease recurrence in thoracic malignancies. These findings support the investigation of FLT-PET-CT in a larger prospective study.